Використання комп'ютерного зору для стеження за морганням очей - Руденко, В. О. (ХНУРЕ, 2020)
The given work is devoted to the ability to monitor eye blinking of people with disabilities, especially for those who are paralyzed, who can only move their eyes. The aspect ratio of the eyes is a much more elegant solution, which includes a very simple calculation based on the ratio of the distances between the facial landmarks of the eyes. This blink detection method is fast, efficient and easy to implement.
Keywords: комп`ютерний зір; око